Codon bias and the folding dynamics of the cystic fibrosis transmembrane conductance regulator. Issue 1 (December 2016) - Bartoszewski, Rafal; Króliczewski, Jaroslaw; Piotrowski, Arkadiusz; Jasiecka, Anna; Bartoszewska, Sylwia; Vecchio-Pagan, Briana; Fu, Lianwu; Sobolewska, Aleksandra; Matalon, Sadis; Cutting, Garry; Rowe, Steven; Collawn, James
Abstract Synonymous or silent mutations are often overlooked in genetic analyses for disease-causing mutations unless they are directly associated with potential splicing defects. More recent studies, however, indicate that some synonymous single polynucleotide polymorphisms (sSNPs) are associated with changes in protein expression, and in some cases, protein folding and function. The impact of codon usage and mRNA structural changes on protein translation rates and how they can affect protein structure and function is just beginning to be appreciated. Examples are given here that demonstrate how synonymous mutations alter the translational kinetics and protein folding and/or function. The mechanism for how this occurs is based on a model in which codon usage modulates the translational rate by introducing pauses caused by nonoptimal or rare codons or by introducing changes in the mRNA structure, and this in turn influences co-translational folding. Two examples of this include the multidrug resistance protein (p-glycoprotein) and the cystic fibrosis transmembrane conductance regulator gene (CFTR). CFTR is also used here as a model to illustrate how synonymous mutations can be examined usingin silico predictive methods to identify which sSNPs have the potential to change protein structure. The methodology described here can be used to help identify "non-silent" synonymous mutations in other genes.